Treatment of skewed multi-dimensional training data to facilitate the task of engineering neural models - Altun, H.; Bilgil, A.; Fidan, B. C. (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Successful application of neural network models relies heavily on problem-dependent internal parameters. As the theory does not facilitate the choice of the optimal parameters of neural models, these can solely be obtained through a tedious trial-and-error process. The process requires performing multiple training simulations with various network parameters, until satisfactory performance criteria of a neural model are met. In literature, it has been shown that neural models are not consistently good in prediction under highly skewed data. Consequently, the cost of engineering neural models rises in such circumstance to seek for appropriate internal parameters. In this paper the aim is to show that a recently proposed treatment of highly skewed data eases the task of practitioners in engineering neural network models to meet satisfactory performance criteria. As the applications of neural models grows dramatically in diverse engineering domains, the understanding of the treatment show indispensable practical values. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: multi-dimensional data treatment; skewness; artificial neural networks; multilayered perceptron; back propagation; suspended sediment prediction; SEDIMENT TRANSPORT; LOAD TRANSPORT; REGRESSION; NETWORK; Computer Science; Engineering; Operations Research & Management Science